Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1093/mnras/stz938
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the nature of compact object in the LMXB MAXI J1957+032 using Swift-xrt

Abstract: MAXI J1957+032 is a transient Low-mass X-ray binary (LMXB) that underwent four short outbursts in 1.5 years since its discovery in 2015. The nature of the compact object in MAXI J1957+032 is not clear, but it was proposed to be a neutron star based on the short-duration of its outbursts. Here, we report the results obtained after performing spectral analysis using data obtained with the X-ray telescope aboard the Neil Gehrels Swift satellite. When describing the spectrum with an absorbed power law, we found th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
2
6
0
Order By: Relevance
“…Three sources, i.e., 1RXS J180408.9-342058, EXO 1745-248 and IGR J17361-4441 are from Parikh et al (2017). MAXI J1957+032 is from Beri et al (2019). Twelve sources in the sample (except for IGR J17494-3030, XTE J1719-291 and IGR J17361-4441 in the sample) are confirmed as NS binaries since the Type I X-ray bursts have been observed.…”
Section: Comparison With Observations For the Anti-correlationmentioning
confidence: 83%
See 1 more Smart Citation
“…Three sources, i.e., 1RXS J180408.9-342058, EXO 1745-248 and IGR J17361-4441 are from Parikh et al (2017). MAXI J1957+032 is from Beri et al (2019). Twelve sources in the sample (except for IGR J17494-3030, XTE J1719-291 and IGR J17361-4441 in the sample) are confirmed as NS binaries since the Type I X-ray bursts have been observed.…”
Section: Comparison With Observations For the Anti-correlationmentioning
confidence: 83%
“…By comparing with a sample of non-pulsating NS-LMXBs with well measured Γ (obtained by fitting the observed X-ray spectrum between 0.5 and 10 keV with a single power law) in the range of L 0.5−10keV ∼ 10 34 − 10 36 erg s −1 , we find that indeed only a small value of 0.003 f th 0.1 is needed to match the observed anti-correlation between Γ and L 0.5−10keV . The data in the sample are searched from literatures, which are summarized at Table 1 of Wijnands et al (2015), Appendix of Parikh et al (2017) and Beri et al (2019) respectively. Theoretically, in our model, there are two components, i.e., a thermal component and a power-law component, both of which can contribute a fraction of the X-ray luminosity between 0.5 and 10 keV respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Swift/XRT observations on June 20, 2022, suggested spectral properties consistent with the 2016 outburst of the source (see, e.g. Beri et al 2019). Moreover, Swift/UVOT detected the UV counterpart of the source, with a magnitude UVW2 = 20.37 ± 0.08 (Beri et al 2022).…”
Section: Introductionmentioning
confidence: 90%
“…Instead, it is suggested to be a possible triple system, with the main-sequence counterpart likely being in a wide orbit around a compact interacting binary. Moreover, the spectral evolution investigated by combining the Swift observations collected during the four outbursts suggested that, for a distance of the order of 4 kpc, a neutron star (NS) might be hosted in the binary system (Beri et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Further, in Qiao & Liu (2020b), based on the sample of nonpulsating NS-LMXBs in Wijnands et al (2015), and adding some more non-pulsating NS-LMXBs from Parikh et al (2017) and Beri et al (2019), we explain the anticorrelation between the Xray photon index Γ (obtained by fitting the X-ray spectra between 0.5 and 10 keV with a single power law) and L 0.5−10keV , i.e., the softening of the X-ray spectra with decreasing L 0.5−10keV , in the range of L 0.5−10keV ∼ 10 34 − 10 36 erg s −1 by adjusting the value of f th . Moreover, it is shown that a fraction of the sources in Qiao & Liu (2020b) are once reported to be fitted with the twocomponent model (with XMM − Newton X-ray data), i.e., a thermal soft X-ray component plus a power-law component.…”
Section: A Summary On Qiao and Liu 2020abmentioning
confidence: 99%